Enjoy your life! - al-'Areefi, Muhammad Abdur-Rahman; Mohammad Elshinawy (International Islamic Publishing House (IIPH), 2012)
"This is an exquisite cllection of incidents from the life of the Prophet, stories from Islamic Heritage, and thought-provoking anecdotes from the life of the author. The aim of the book is to train the reader to enjoy living his life by practicing various self-development and inter-personal skills. ..., in order to highlight the benefit ofusing social skills, the author draws from the lives of the Prophet and his Companions. ..."--Page [4] of cover